Clinical and genetic analysis of benign familial infantile epilepsy caused by PRRT2 gene variant - Gu, Yu; Mei, Daoqi; Wang, Xiaona; Ma, Ang; Kong, Jinghui; Zhang, Yaodong (Frontiers in Neurology, 2023)
Objective This study presents the clinical phenotypes and genetic analysis of seven patients with benign familial infantile epilepsy (BFIE) diagnosed by whole-exome sequencing. Methods The clinical data of seven children with BFIE diagnosed at the Department of Neurology, Children’s Hospital Affiliated to Zhengzhou University between December 2017 and April 2022 were retrospectively analyzed. Whole-exome sequencing was used to identify the genetic causes, and the variants were verified by Sanger sequencing in other family members. Results The seven patients with BFIE included two males and five females ranging in age between 3 and 7 months old. The main clinical phenotype of the seven affected children was the presence of focal or generalized tonic–clonic seizures, which was well controlled by anti-seizure medication. Cases 1 and 5 exhibited predominantly generalized tonic–clonic seizures accompanied by focal seizures while cases 2, 3, and 7 displayed generalized tonic–clonic seizures, and cases 4 and 6 had focal seizures. The grandmother and father of cases 2, 6, and 7 had histories of seizures. However, there was no family history of seizures in the remaining cases. Case 1 carried a de novo frameshift variant c.397delG (p.E133Nfs*43) in the proline-rich transmembrane protein 2 (PRRT2) gene while case 2 had a nonsense variant c.46G > T (p.Glu16*) inherited from the father, and cases 3–7 carried a heterozygous frameshift variant c.649dup (p.R217Pfs*8) in the same gene. In cases 3 and 4, the frameshift variant was de novo, while in cases 5–7, the variant was paternally inherited. The c.397delG (p.E133Nfs*43) variant is previously unreported. Conclusion This study demonstrated the effectiveness of whole-exome sequencing in the diagnosis of BFIE. Moreover, our findings revealed a novel pathogenic variant c.397delG (p.E133Nfs*43) in the PRRT2 gene that causes BFIE, expanding the mutation spectrum of PRRT2.